Stroke After Emergent Surgery for Acute Type a Aortic Dissection - Allam, Mohamed; Badr Soliman, Said Abdelaziz; Elsharkawy, Ahmed Abdelaziz; Abdelaal, Amr Mahmmoud; Gamal, Mahmoud; Adas, Ahmed (Journal of Neonatal Surgery, 2025)
Background: Cerebral ischemia in acute type A aortic dissection (ATAAD) is primarily attributed to hypotension, reduced blood flow to the brain as a result of thromboembolism and real lumen blockage. If we want to improve patient outcomes, we need to know what factors increase the risk of postoperative stroke and how those factors affect neurological recovery and morbidity. Aim: Finding factors that increase the risk of postoperative stroke and studying how those factors affect neurological recovery and morbidity were the goals of this research following emergent surgical repair of ATAAD. Patients and Methods: A non-randomized prospective with fifty individuals diagnosed with ATAAD participated in the research. who underwent emergent surgical repair at Kasr Al-Ainy Hospital, Faculty of Medicine, Cairo University. The study assessed risk factors associated with postoperative stroke, including surgical techniques, perfusion strategies, and patient-specific variables. Results: The supra-coronary repair method showed a trend toward association with postoperative stroke, yet the result was not noteworthy from a statistical standpoint (p = 0.123). Likewise, there was no statistically significant relationship between circulatory stoppage and stroke after surgery (p = 0.255). Stroke incidence was, however, substantially correlated with retrograde cerebral perfusion (p = 0.001). A significant risk factor for stroke was found to be femoral cannulation. There was a greater frequency of severe carotid stenosis (p ≤ 0.007) and considerably higher blood triglyceride levels (p < 0.001) in patients who had a stroke after surgery. Patients with a stroke had a much higher death rate (75%) than those without a stroke (9.5%; p = 0.01). Conclusion: Stroke after ATAAD surgery is related with a higher risk of death, particularly in older individuals, those with elevated serum triglyceride levels, and those with significant carotid stenosis. These findings highlight the importance of preoperative risk stratification and tailored surgical strategies to mitigate stroke risk